Antiproliferative activity of bruceajavanica fruits extract towards hela cancer cell lines - Maslinda, Mansor (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Fruits of Brucea javanica (B. javanica) has been used as a folk remedy in Chinese medicine, and it has been shown to exhibit antiamoebic, antimalarial, antiplasmodial, antileukaemic and anticancer. In this study, B. javanica fruit (BJF) were extracted using petroleum ether, methanol and distilled water as solvent. All three crude extract were treated on human cervical adenoma cell line, HeLa and human breast cancer cell line, MCF-7. All the extract showed ICso value less than lOOflg/ml and methanol crude extract on HeLa cells were given the best ICso value with 2.8 f.tg/ml. Thus, HeLa cells were selected to undergo microscopic analysis examination using methanol crude extract of BJF. The analysis of cellular morphology and nuclei morphology on treated HeLa cells at 24, 48 and 72 h were done by Hematoxylin and Eosin (H&E) staining and Hoechst 33258 staining, respectively. The typical apoptosis characteristics were observed in H&E stain. The apoptotic indexes ofBJF-treated cells were revealed almost similar degree ofapoptosis at time dependent manner compare with positive control, tamoxifen. These results proposed that BJF exhibits antiproliferative effect on HeLa cells via inducing-apoptosis. Therefore, it may be a potential candidate in field of anticancer drug discovery.